2021
DOI: 10.3390/polym13132207
|View full text |Cite
|
Sign up to set email alerts
|

Biomethane Yield, Physicochemical Structures, and Microbial Community Characteristics of Corn Stover Pretreated by Urea Combined with Mild Temperature Hydrotherm

Abstract: The corn stover (CS)’s compact structure makes it challenging for microorganisms to use in anaerobic digestion (AD). Therefore, improving CS biodegradability has become a key focus in AD studies. Methods are being targeted at the pretreatment of CS, combining advanced urea with mild temperature hydrotherm pretreatment to study its effect on promoting the AD process of CS. The biomethane yield, physicochemical structure, and microbial community characteristics were investigated. CS samples were assigned into gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Specifically, at the genus level, we found that the addition of pectin increased the relative abundances of Clostridium sensu_strict_1, Terrisporobacter, unclassified_f_ Peptostreptococcaceae, Subdoligranulum, and Faecalibacterium. Clostridium_sensu_stricto_1 and Terrisporobacter may directly ferment polysaccharides to SCFAs (Niu et al, 2015;Lu et al, 2021). Besides, Faecalibacterium and Subdoligranulum are also the major butyrate and Lactic producers in the hindgut (Holmstrom et al, 2004;Bjerrum et al, 2006;Louis and Flint, 2009) which echoes the above that SCFAs were rich in cecal chyme.…”
Section: Discussionmentioning
confidence: 77%
“…Specifically, at the genus level, we found that the addition of pectin increased the relative abundances of Clostridium sensu_strict_1, Terrisporobacter, unclassified_f_ Peptostreptococcaceae, Subdoligranulum, and Faecalibacterium. Clostridium_sensu_stricto_1 and Terrisporobacter may directly ferment polysaccharides to SCFAs (Niu et al, 2015;Lu et al, 2021). Besides, Faecalibacterium and Subdoligranulum are also the major butyrate and Lactic producers in the hindgut (Holmstrom et al, 2004;Bjerrum et al, 2006;Louis and Flint, 2009) which echoes the above that SCFAs were rich in cecal chyme.…”
Section: Discussionmentioning
confidence: 77%